Influence of sparger type and regime of fluid on biomass and lipid productivity of Chlorella vulgaris culture in a pilot airlift photobioreactor - López-Hernández, Yaremi (Array, 2019)
The effect of different types of spargers and the influence of the air flow rate on biomass and lipids production by Chlorella vulgaris was evaluated. These data allowed correlation of the hydrodynamic behavior of the photobioreactor with the byproducts production. The hydrodynamic characterization was developed by determining the mixing time (tM), hold-up, and total volumetric mass transfer coefficient of CO2, kLa(CO2)T, at increasing air flow rates for three different spargers: star-shaped, cross-shaped and porous glass surface sparger. The hydrodynamic characterization showed that the tM decreased, while the hold-up values and the kLa(CO2)T increased as a result of the increment in the volumetric air flow rate between 5 to 17 L min–1. The highest biomass and lipid concentrations were determined at the higher aeration rate (20 L min–1), which was correlated with the lower tM, the higher hold-up and kLa(CO2)T values. Biomass and lipid production showed an inverse correlation. The highest biomass concentration (750 mg L–1) and the lowest lipid concentration (10 mg L–1) were measured with the star sparger. In contrast, when the lowest biomass concentration was obtained (240 mg L–1), the highest lipid concentration of 196 mg L–1 was measured with the glass sparger. The maximum biomass productivity values were determined at the lower aeration rate and the star sparger, with the minimum power per unit of volume, which could be useful for a cost-effective process.